Improving the self‐efficacy, knowledge, and attitude of nurses regarding concurrent disorder care: Results from a prospective cohort study of an interprofessional, videoconference‐based programme using the ECHO model. (27th October 2022) - Chicoine, Gabrielle; Côté, José; Pepin, Jacinthe; Dyachenko, Alina; Fontaine, Guillaume; Jutras‐Aswad, Didier
Abstract: Several challenges have been identified for patients with concurrent disorders to access adequate services and for nurses to care for them. These challenges contribute to a pressing need for continuing educational interventions, particularly within the mental health nursing workforce. To address this issue, an innovative interprofessional videoconferencing programme based on the ECHO® model ( Extension for Community Healthcare Outcomes ) was implemented in Quebec, Canada to support and build capacity among healthcare professionals for CD management. The aim of this prospective cohort study was to examine nurses' self‐efficacy, knowledge, and attitude scores over a 12‐month period. All nurses who registered in the programme between 2018 and 2020 were invited to participate in the study ( N = 65). The data were collected online using a self‐administered survey at baseline, after 6 months, and then 12 months following entry‐to‐programme. Twenty‐eight nurses participated in the study (96.4% women), with a mean age of 39.1 (SD = 6.2). Compared to other professions ( n = 146/174), the group of nurses also showed significant improvements in their knowledge and attitude scores, with respective effect sizes of 0.72 and −0.44 at 6 months, and 0.94 and −0.59 at 12 months. However, significant changes in self‐efficacy were only found at the 12‐month follow‐up ( P = 0.0213), among the nurses who attended more than 25% of the 20‐session curriculum. ECHO is a promising intervention to improve the accessibility of evidence‐based practice and to support nurses in suitably managing concurrent disorders. Further research is needed to establish the effectiveness of this educational intervention on clinical nursing practice and patient outcomes.